Ghrelin did not change coronary angiogenesis in diet-induced obese mice - Khazaei, M.; Tahergorabi, Z. (Cellular and Molecular Biology, 2017)
Ghrelin is a 28 amino acids peptide that initially was recognized as an endogenous ligand for growth hormone secretagogue receptor (GHSR). Recently, a number of studies demonstrated that ghrelin is a cardiovascular hormone with a series cardiovascular effect. The main objective of this study was to investigate the effect of systemic ghrelin administration on angiogenesis in the heart and its correlation with serum leptin levels in normal and diet-induced obese mice. 24 male C57BL/6 mice were randomly divided into four groups: normal diet (ND) or control, ND+ghrelin, high-fat-diet (HFD) or obese and HFD+ghrelin (n=6/group). Obese and control groups received HFD or ND, respectively, for 14 weeks. Then, the ghrelin was injected subcutaneously 100µg/kg twice daily. After 10 days, the animals were sacrificed, blood samples were taken and the hearts were removed. The angiogenic response in the heart was assessed by immunohisochemical staining. HFD significantly increased angiogenesis in the heart expressed as the number of CD31 positive cells than standard diet. Ghrelin did not alter angiogenesis in the heart in both obese and control groups, however, it reduced serum nitric oxide (NO) and leptin levels in obese mice. There was a strong positive correlation between the number of CD31 positive cells and serum leptin concentration (r=0.74). Leptin as an angiogenic factor has a positive correlation with angiogenesis in the heart. Although systemic administration of ghrelin reduced serum leptin and NO levels in obese mice, however, it could not alter coronary angiogenesis.